Pengaruh Kinerja Lingkungan dan Pengungkapan Lingkungan Terhadap Nilai Perusahaan Sektor Consumer Goods di BEI - Nurmadi Harsa Sumarta; Natasha Milani; Edy Supriyono (ITB AAS INDONESIA, 2023)
This study was designed to proffer evidential support for the influence of environmental performance on firm value and environmental disclosure on the value of consumer goods sector companies listed on the Indonesia Stock Exchange. The independent variable measurement of environmental performance in this research is based on the PROPER grading system, which varies in grades on a scale of 1 to 5. Meanwhile, the technique of assessing environmental disclosure is made using the environmental aspects of the GRI. The data sample consists of 22 companies within the consumer goods industry from 2017 to 2021, with a total processed sample amounting to 110 data points. The processing method involves multiple linear regressions with a random effects model (REM). Data processing using Eviews 12 shows that environmental performance positively affects firm value and environmental disclosure negatively affects firm value.